Experience and Readiness of Elementary School Teachers in Serang Regency in Implementing Learning with a Deep Learning Approach - Paidi Paidi; Ahmad Kamal Sudrajat; Mualimin; Himmatul Hasanah; Siti Nurkhayati (UIN Raden Mas Said Surakarta, 2025)
The purpose of this study was to examine the experiences and readiness of elementary school teachers in Serang Regency to implement a deep learning approach. This study was a survey. Participants were 44 elementary school teachers in Karangwatu District, Serang Regency. The results showed that teachers’ readiness to implement deep learning was in the moderate category. Teachers’ readiness to use learning technology was also in the moderate category. Teachers’ experiences in implementing deep learning aspects were not well structured, even though they had identified themselves as using them in the classroom. Stakeholders can use the results of this study to design deep learning training that suits the needs of elementary school teachers.